EARLY CAMBRIAN PRIAPULID WORMS BURIED WITH THEIR LINED BURROWS - Zhang X.G.; Hou X.G.; Bergström J. (My University, 2006)
Five specimens of the priapulid Maotianshania cylindrica preserved inside their lined burrows were described from the Lower Cambrian Chengjiang deposits near Kunming, southern China. The exceptional preservation suggests that this worm made a dwelling tube by lining within the uppermost sediment layers. This seems to be unique among priapulids in comparison with the Cambrian Selkirkia and Paraselkirkia, as well as some modern priapulid larvae and loriciferans. Taphonomic evidence indicates that the burrow-and-worm specimens are not buried in situ but were moved by storm, tsunami, or turbidity generated currents that are thought to have brought sedimentary material intermittently. © 2006 Cambridge University Press.
Keywords: BEHAVIOUR; EARLY CAMBRIAN; LINED BURROW; PRIAPULIDS; TAPHONOMY; Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская